Pengaruh waktu ekstraksi menggunakan ultrasonic assisted extraction terhadap antosianin jantung pisang (Musa spp) - Dianasri Widyapuri; Ike Sitoresmi Mulyo Purbowati; Condro Wibowo (Agroindustrial Technology, University of Trunojoyo Madura, 2022)
Banana blossom is a source of anthocyanin that is potentially utilized as natural dyes in the food industry. Anthocyanin from banana blossom can be extracted using Ultrasonic Assisted Extraction (UAE) and maceration method. Extraction using ultrasonic causes cavitation effect thereby provide an efficiency of extraction time if compared with maceration method. This study aimed to determine the effect of the duration of sonication treatment on total anthocyanin in banana blossom extract. Experimental design applied in this research is randomized block design with five treatments: maceration for 24 hours, sonication: 5 minutes, 10 minutes, 15 minutes and 20 minutes. Sonication was carried out at 40 kHz. Parameters determined were anthocyanin content, color (L*, a*, b*), morphological structure and total soluble solid. The results showed that sonication time did not significantly affect the total anthocyanin of banana blossom extract. Total anthocyanin of banana blossom extract with sonication time treatment ranged from 86.32 mg/L to 87.31 mg/L. The selected treatment for banana blossom extraction using UAE was 5 minutes sonication. This treatment resulted in a total anthocyanin concentration of 87.31 mg/L, which has comparable to the 24 hours maceration method. The color parameter (L*, a*, b*) and total soluble solid of the banana blossom extract with 5 minutes sonication was 28.67, 12.54, 17.92 and 8.32 %Brix, respectively. Meanwhile, the morphological structure showed formation of pores on the surface of banana blossom cells.